Observations on the Seed Viability of Sal (Shorea robusta) - Prasad, Ram; Jalil, Parvez (Indian Forester, 1987)
An experiment to test the viability of freshly collected sal seeds (1985) from trees of different girth classes was undertaken. Sal seed was collected from Amarkantak (Distt. Shahdol). Some seeds were also stored in air-tight polythene bags for about two months 10 test their viability. It was observed that the deterioration in Sal seed takes place very fast unless it is properly stored. Severe insect damage to sal seeds appears to be responsible for the loss of seed viability.